Surgical Outcome of Medial Rectus Resection in Recurrent Exotropia: A Novel Surgical Formula - Abbie Sheung-Wan Luk; Jason Cheuk-Sing Yam; Henry Hing-Wai Lau; Wilson Wai-Kuen Yip; Alvin Lerrmann Young (Journal of Ophthalmology)
Purpose. To evaluate the surgical outcomes of unilateral or bilateral medial rectus (MR) muscle resection for recurrent exotropia after bilateral lateral rectus (BLR) muscle recession based on a novel surgical formula. Methods. Forty-one consecutive patients with unilateral or bilateral MR muscle resection for recurrent exotropia after BLR muscle recession were included in this retrospective study. All surgeries were performed according to the formula: 1.0 mm MR muscle resection for every 5 prism dioptres (PD) of exotropia, with an addition of 0.5 mm to each MR muscle operated on. Results. The mean recurrent exotropia distant deviation was 28 PD ± 11.2 (range 14 to 55 PD). Overall at postoperative 1 month, 36 (88%) achieved successful outcomes, 4 (10%) had undercorrection, and 1 (2%) had overcorrection. At postoperative 6 months, 29 (71%) achieved successful outcomes, 12 (29%) had undercorrection, and none had overcorrection. Subgroup analysis showed no statistically significant difference in success rates between unilateral and bilateral MR groups. Conclusion. Unilateral or bilateral MR muscle resection using our surgical formula is a safe and effective method for calculating the amount of MR resection in moderate to large angle recurrent exotropia, with a low overcorrection rate.